Yield, Economic Benefit, Soil Water Balance, and Water Use Efficiency of Intercropped Maize/Potato in Responses to Mulching Practices on the Semiarid Loess Plateau - Junhong Xie (MDPI AG, 2021)
Increasing agricultural productivity without undermining further the integrity of the Earth’s environmental systems such as soil water balance are important tasks to ensure food security for an increasing global population in rainfed agriculture. The impact of intercropping maize (Zea mays L.) with potato (Solanum tuberosum L.) on yield, land equivalent ratios (LER), water equivalent ratio (WER), water use, energy output, and net economic return were examined under seven planting systems: potato grown solely or intercropped on the flat field without mulching, maize grown solely or intercropped with potato on ridges or flat field with or without plastic film mulched. The three intercropping systems had 3–13% less water use than the monocropping. Among the intercropped systems, flat field caused more depletion of soil water than ridged field for both years. Compared to monocultures, intercropping with plastic film mulching and ridging significantly increased LER and WER. Meanwhile, intercropping with mulching and ridging significantly increased net economic return and energy output by 8% and 24%, respectively, when compared to monocropping. These results suggest that maize under plastic film mulched ridge-furrow plot intercropped with potato under flat plot without mulching increased energy output, net economic return, and water use efficiency without increasing soil water depletion, which could be an optimal intercropping system for the semiarid farmland on the western Loess Plateau.